PENGARUH LEAFLET FISIKA BERORIENTASI STRATEGI PEMBELAJARAN KONTEKSTUAL TERHADAP KOMPETENSI FISIKA SISWA SMA NEGERI 4 PADANG - Saint Saputra; Asrizal Asrizal; Harman Amir (Universitas Negeri Padang, 2016)
Physics is an important in learning school. Physics also can foster thinking skills of learners useful to solve problems in everyday life. With this basic, learners should master the physics well. Reality shows low learning outcomes of students. One solution to the problem is an interesting teaching materials and related to everyday life, so the purpose of the study was to investigate the influence of Physics leaflets oriented contextual learning strategy for the competence of students of class X SMAN 4 Padang. The research is a form of quasi-experimental design with randomized control group. The study population was the students of class X SMAN 4 Padang in the second semester of Academic Year 2015/2016. The sample of the research use purposive sampling. Data Physics research is an achievement of competencies learners. Data Physics research is an achievement of competencies learners. Competence competence learners include attitudes , knowledge , and skills. Competence attitude is measured using observation sheets, competency knowledge using a written test and skill competencies measured using performance assessment rubric. The data obtained is converted to the value of the score and then performed a descriptive statistical analysis , normality test, homogeneity , and two comparative test average. Based on data analysis that has been done, it can be argued these results. As a result of the research is application -oriented Leaflet contextual learning strategy provides significant influence on the attitude of competence, knowledge, and skills at the level of 95 %. Therefore Leaflet physics oriented contextual learning strategy is best applied to support learning in high school Physics